Assessment of Quality of Sexual Life in Male Patients with Psoriasis - Aslam, Azmiree Binte; Khan, Rashed Mohammad; Abdullah, Md Shayekh; Khan, Md Alauddin (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Psoriasis is a global burden of disease characterized by the presence of well circumscribed erythematous papule & plaque of various size & shape, covered by silvery scales. It not only hampers the quality of life but also hampers the sexual function. Men who have psoriasis may be more likely to have sexual problems, such as sexual apathy, orgasmic dysfunction, erectile dysfunction (ED), etc. Stress tends to be a triggering or aggravating factor in psoriasis. In addition, the disease itself can generate emotional stress because of its lesions. It is thought that chronic inflammation. Results in metabolic diseases and proinflammatory cytokines give rise to the development of atherogenesis. Pelvic arterial atherosclerosis is another cause of sexual dysfunction. This study was designed to determine the impact of moderate to severe psoriasis on quality of life and sexual dysfunction in male patients. Methods: This case control study was conducted in Department of Dermatology and Venereology, Dhaka Medical College Hospital, among the 100 patients. Group- A was cases (male married patients age between 24 years and 60 years with history of moderate to severe psoriasis) and group-B were control (male married patients age between 24 years and 60 years without psoriasis). Then variables were analyzed and compared. Data was processed and analyzed with the help of computer program SPSS and Microsoft excel. Quantitative data expressed as mean and standard deviation and qualitative data as frequency and percentage. Comparison was done by tabulation and graphical presentation in the form of tables, pie chart, graphs, bar diagrams, histogram & charts etc. Results: It was found that majority of the patients i.e. 46% were between 34-43 years, mean age was found to 41.7±11.3 years. No significant difference in age and other demographic profile was observed between groups. Prevalence of IHD (8.0%), stroke (14.0%), dyslipidaemia (54.0%), neuropathy (26.0%) and PVD (8.0%) were higher in case or psoriatic patients. On evaluation of Dermatology Life Quality Index (DLQI), majority of patients (54%) score was 6-10, followed by 24.0% had score 2-5 and 22.0% of patients had score 11-20 or very large effect on patient’s life. Prevalence of erectile dysfunction was 36.0%, prevalence of orgasmic dysfunction was 24.0%. On multivariate analysis which was done by ordinal logistic regression procedure. The attributes found to be positively associated with sexual dysfunction severity in the multivariate model were patient’s age, disable status, sedentary work, duration of illness, etc. Conclusion: Erectile dysfunction and orgasmic dysfunction are common in psoriatic male patients. There is association with other comorbidities. J Bangladesh Coll Phys Surg 2022; 40: 233-228